2018
DOI: 10.37358/rc.18.7.6394
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal-induced Cuticular Alkane Changes of Tall Fescue (Festuca arundinacea) Plantlets

Abstract: Heavy metal pollution of ecosystems is of great concern, due to the persistence of metals in ecosystem. In this regard, the mountainous pastures of Romanian Carpathians, especially those in the areas of abandoned mines, need particular attention. The aim of this work was to assess the effect of heavy metals and metalloids exposure on cuticular wax composition of tall fescue leaves (Festuca arundinacea). Therefore, we have particularly investigated the variations of long chain hydrocarbon fractions, which are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In this study we showed that two noxious metal ions can bind to anti-amyloid peptides. Heavy metals, including copper and iron, are environmental contaminants that cannot be degraded or destroyed [10,29]. Their biological effect differs from that of organic pollutants such as dinitrophenols [30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we showed that two noxious metal ions can bind to anti-amyloid peptides. Heavy metals, including copper and iron, are environmental contaminants that cannot be degraded or destroyed [10,29]. Their biological effect differs from that of organic pollutants such as dinitrophenols [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, altered metal homeostasis can be one of the factors causing those disorders. Besides, redox active metals such as cooper and iron carry pro-oxidant properties that induce oxidative stress by generating reactive oxygen species (ROS) [9,10]. Most of the reactions involving redox active metals are related to Fenton chemistry that includes a series of reactions that initiates with hydrogen peroxide and leads to the formation of highly unstable radicals that affect biological macromolecules [5].…”
mentioning
confidence: 99%
“…Important changes in the concentration of cuticular alkane of tall fescue plants (Festuca arundinacea) induced by the presence of heavy metal ions was also recently reported [4]. These authors showed that multiple mechanisms may exist through which the tested plants could develop and adapt when exposed to various chemicals characterized by different degrees of toxicity.…”
mentioning
confidence: 83%
“…These authors showed that multiple mechanisms may exist through which the tested plants could develop and adapt when exposed to various chemicals characterized by different degrees of toxicity. Thus, significant differences were observed between the * emails: carmeniacoban@ymail.com, darjailieva@abv.bg, gabidr@uaic.ro results from Ba 2+ , Pb 2+ and Fe 2+ and those with AsO 4 3and Cu 2+ , and these ions are characterized by different degrees of toxicity. However, most of heavy metal ions react with thiol-containing peptides and proteins, which may protect the cells against metal toxicity [5].…”
mentioning
confidence: 99%
“…Oxidative stress is an important aspect of this pathology and is one of the first signs of Alzheimer's disease. However, its exact role of ROS in AD is not known, it still unclear what is the initial source of oxidation stress in AD, and a supposition says it could be related to redox-active metals such as copper or iron [2,3]. Is known that numerous effects of oxidative stress causes the appearance of ROS [4].…”
mentioning
confidence: 99%